Optimization of Bi2O3, TiO2, and Sb2O3 doped ZnO-based low-voltage varistor ceramic to maximize nonlinear electrical properties - Dorraj, Masoumeh; Zakaria, Azmi; Abdollahi, Yadollah; Hashim, Mansor; Moosavi, Seyedehmaryam (Hindawi Publishing Corporation, 2014)
In ZnO-based low voltage varistor, the two essential features of microstructure determining its nonlinear response are the formation Bi-enriched active grain boundaries as well as a controlled ZnO grain size by secondary spinel-type phases. Besides, the microstructure and phase composition are strongly affected by the dopant concentration during sintering process. In this study, the optimal dopant levels of Bi2O3, TiO2, and Sb2O3 to achieve maximized nonlinear electrical property (alpha) were quantified by the response surface methodology (RSM). RSM was also used to understand the significance and interaction of the factors affecting the response. Variables were determined as the molar ratio of Bi2O3, TiO2, and Sb2O3. The alpha was chosen as response in the study. The 5-level-3-factor central composite design, with 20 runs, was used to conduct the experiments by ball milling method. A quadratic model was established as a functional relationship between three independent variables and alpha. According to the results, the optimum values of Bi2O3, TiO2, and Sb2O3 were obtained 0.52, 0.50, and 0.30, respectively. Under optimal conditions the predicted alpha (9.47) was calculated using optimal coded values from the model and the theoretical value is in good agreement with the value (9.43) obtained by confirmation experiment.